A sort of revolution: Systematics and physical anthropology in the 20th century. Issue 4 (25th March 2018) - Cartmill, Matt
Abstract: During the first four decades of the 20th century, a system of ideas about the evolution and systematics of humans and other primates coalesced around the work of George Gaylord Simpson and W. E. Le Gros Clark. Buttressed by the "new physical anthropology" of the 1950s, that system provided an authoritative model—a disciplinary matrix or paradigm—for the practice of that aspect of biological anthropology. The Simpson‐Le Gros Clark synthesis began to unravel in the 1960s and collapsed in the 1970s under the onslaught of cladistic systematics. The cladistic "revolution" resembles a paradigm shift of the sort proposed by Thomas Kuhn because it was driven, not by new biological discoveries or theories, but by a change in aesthetics.